STeM: a web-based system for managing test artifacts in software testing course / Nor Shahida Mohamad Yusop, Adib Suhaimi Mohd Fikri and Nursyuhaila Yahaya - Yusop, Nor Shahida Mohamad; Mohd Fikri, Adib Suhaimi; Yahaya, Nursyuhaila (Universiti Teknologi MARA, Pulau Pinang, 2022)
With the increasing demand for sophisticated and cost-effective software testing, many software industries are looking for highly skilled software testers. To meet that demand, many universities have offered software testing courses in their software engineering programmes. At the Faculty of Computer and Mathematical Sciences Universiti Teknologi MARA, a software testing course was offered to Bachelor of Information System Engineering students in semester 5. As part of the course assessment, students are required to conduct system tests in which they need to design, execute, and document test cases. Currently, the use of Microsoft Word and Excel Spreadsheet to document test cases and test results are not effective for test case management. The most common problems experienced by the students when using Microsoft Word to manage test cases are: 1) difficulty to ensure document consistency when various team members update the test artifacts, 2) unable to track and monitor the test status when the test results are kept individually, and 3) improper test-requirements traceability, since separate traceability documents need to be maintained and updated throughout the development life cycle. This paper reports on the development of STeM web-based system to assist the test case management in a software testing course. The STeM serves as a collaborative platform for the students to build test cases, create requirements traceability, record test cases results, monitor test case status, and produce test reports. In addition, the lecturer can monitor the test progress through this system too